Reliability of single and paired‐pulse transcranial magnetic stimulation in the vastus lateralis muscle. Issue 4 (14th August 2015) - O'leary, Thomas J.; Morris, Martyn G.; Collett, Johnny; Howells, Ken
ABSTRACT Introduction: Transcranial magnetic stimulation (TMS) is an important tool to examine neurological pathologies, movement disorders, and central nervous system responses to exercise, fatigue, and training. The reliability has not been examined in a functional locomotor knee extensor muscle. Methods: Within‐ (n = 10) and between‐day (n = 16) reliability of single and paired‐paired pulse TMS was examined from the active vastus lateralis. Results: Motor evoked potential amplitude and cortical silent period duration showed good within‐ and between‐day reliability (intraclass correlation coefficient [ICC] ≥ 0.82). Short‐ and long‐interval intracortical inhibition (SICI and LICI, respectively) demonstrated good within‐day reliability (ICC ≥ 0.84). SICI had moderate to good between‐day reliability (ICC ≥ 0.67), but LICI was not repeatable (ICC = 0.47). Intracortical facilitation showed moderate to good within‐day reliability (ICC ≥ 0.73) but poor to moderate reliability between days (ICC ≥ 0.51). Conclusions: TMS can reliably assess cortical function in a knee extensor muscle. This may be useful to examine neurological disorders that affect locomotion. Muscle Nerve 52: 605–615, 2015